Benin : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper discusses a growth-at-risk (GaR) model which is used to compute a distribution of expected GDP growth for Benin. The model predicts growth rates of ~6.7 percent for 2019 and a range of 6.4-6.8 percent in the medium-term (depending on the specification). Risks to future growth are assessed to be tilted to the downside. 2019 GDP growth is estimated around 6.7 percent, on average, across several specifications. The model considers external factors (world trade, global financial conditions, trade policy uncertainty, and US consumer sentiment), country-specific exposures to external factors (commodity terms of trade and trade-partner growth), and domestic factors (domestic financial conditions, fiscal policy, and the exchange rate). The analysis reveals that growth projections estimated both for the median and mode are slightly higher conditioned on 2018 data, yet when expectations about 2019 are considered using World Economic Outlook projections they fall. Overall, risks seem to be tilted to the downside. Medium term growth is estimated at between 6.4 and 6.8 percent. Risks to growth remain tilted to the downside, yet less skewed than in the short term.